Cultural management and its impact on quality performance - Abdul Rahman, Norhayati; Tasmin, Rosmaini (2010)
Studies on cultures have gained significant attention in decades. Such studies are essential due to its impact on organizations and societies.Multiracial communities in the USA have contributed to its development and modernization.As such, the USA strongly influences the world’s economy.In contrast, Japan through its homogeneous racial environment manages to bring the community as a developed country.Thus, this study will investigate the multicultural society in Malaysia.Whether this local environment reflects like the one in the USA or in the Japan cultures.As such, the impact of cultural management practices on organization towards quality performance will be identified. Both quantitative and qualitative approaches will be applied in this research for collecting data.The findings of the research are expected to be a viable reference for multinational firms to perform effectively in multicultural setting.